Goal attainment in mobility after acute rehabilitation of mobility-restricting paralysis syndromes with regard to the ambulatory therapeutic level of participation NeuroMoves - Hug, Andreas; Spingler, Tamara; Hensel, Cornelia; Fichtner, Stefan; Schmittus, Tiziana; Heutehaus, Laura; Wensing, Michel; Rupp, Rüdiger; Weidner, Norbert (BMC neurology, 2021)
A central goal of rehabilitation in patients with paralysis syndromes after stroke or spinal cord injury (SCI) is to restore independent mobility as a pedestrian or wheelchair user. However, after acute rehabilitation, the mobility frequently deteriorates in the ambulatory setting, despite the delivery of rehabilitative interventions such as physical therapy or the prescription of assistive devices. The aim of the NeuroMoves study is to identify factors that are associated with changes of mobility in the ambulatory setting after acute inpatient rehabilitation, with a particular focus on participation according to the ICF (International Classification of Functioning, Disability and Health).
Gesehen am 14.05.2021